2022
DOI: 10.3390/healthcare10061102
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Caregivers of People with Dementia (PwD): Differential Patterns and Implications for Psychological Support

Abstract: Very little attention has been paid to identifying the differential characteristics of primary and secondary dementia caregivers. The aims of this study were: to determine whether differences exist between primary and secondary caregivers of people with dementia (PwD) and to explore the profile of primary and secondary caregivers reporting symptoms of anxiety and/or depression. The participants were 146 caregivers of PwD, 73 primary caregivers and 73 secondary caregivers. The results revealed different pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
1
2
0
1
Order By: Relevance
“…This gender profile is consistent with many studies on dementia in which the caregivers are mainly female (i.e. [20,[78][79][80][81]). Doss et al [82,83] also showed that women are the initiators of couple therapy in 73.2% of cases and that they are more prone to seek conjugal therapy when they are distressed.…”
Section: Acceptability Of Interventionsupporting
confidence: 90%
“…This gender profile is consistent with many studies on dementia in which the caregivers are mainly female (i.e. [20,[78][79][80][81]). Doss et al [82,83] also showed that women are the initiators of couple therapy in 73.2% of cases and that they are more prone to seek conjugal therapy when they are distressed.…”
Section: Acceptability Of Interventionsupporting
confidence: 90%
“…Most of the family caregivers were women, and they had higher dementia grief scores than men. This may be caused because women are also often involved in other tasks, such as child and household care [28,29]. In addition, these caregivers lack free time and often limit their employment to part-time work or even sacrifice their job and opportunities for advancement, affecting family income and financial stability.…”
Section: Discussionmentioning
confidence: 99%
“…Carers should therefore be considered essential partners in the planning and provision of care in all settings according to the wishes and needs of the person with dementia, and they should have access to the support and services tailored to their needs to effectively respond to and manage the physical, mental, and social demands of their caring role. Listening to the voices of the next-of-kin carers as informal carers of dementia sufferers—and increasing, improving, and adapting community-based services—will contribute to reducing the burden [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%